Learning Material Development of Interactive Reading Subject through Dick and Carey - Dewi Sri Kuning; Rulik Setiani (Budapest International Research and Critics University, 2022)
The aims of this research was to develop the teaching material and to know the effectiveness of learning material developments’ result through Interactive Reading subject by using Dick and Carey for third semester students majoring in English education Muhammadiyah University of Kotabumi in academic year 2020/2021. The sites were class 3A which consists of 17 students. This teaching material was developed using DICK and CAREY development procedures which included: 1)Identity Instructional Goal, 2) Conduct Instructional Analysis, 3) Analyze Learners and Contexts, 4) Write Performance Objectives, 5) Develop Assesment Instruments, 6) Develop Instructional Strategy, 7) Develop and Select Instructional Materials, 8) Design and Conduct Formative Evaluation of Instruction, 9) Revise Instruction, and 10) Designing and Implementing Summative Evaluation. Based on the test results, it can be concluded that teaching material that has been developed is very effective for learning Interactive Reading subject. It can be seen by the average score of 3A students got 75.6 higher than the score of 3B was 67.7, while based on the results of questionnaire, the three aspects of teaching material is in very good category.